Isis A History. - Gerges, Fawaz A. (Princeton University Press, 2021)
An authoritative introduction to ISIS--now expanded and revised to bring events up to the presentThe Islamic State stunned the world with its savagery, destructiveness, and military and recruiting successes. However, its most striking and distinctive characteristic was its capacity to build governing institutions and a theologically grounded national identity. What explains the rise of ISIS and the caliphate, and what does it portend for the future of the Middle East? In this book, one of the world's leading authorities on political Islam and jihadism sheds new light on these questions. Moving beyond journalistic accounts, Fawaz Gerges provides a clear and compelling explanation of the deeper conditions that fuel ISIS. This new edition brings the story of ISIS to the present, covering key events--from the military defeat of its territorial state to the death of its leader al-Baghdadi--and analyzing how the ongoing Syrian, Iraqi, and Saudi-Iranian conflict could lead to ISIS's revival.
Description based upon print version of record.
Keywords: IS (Organization); Islamic fundamentalism.; Jihad.; Terrorism -- Religious aspects -- Islam.; Middle East -- Politics and government -- 21st century.; Intégrisme islamique.; Jihād.; Terrorisme -- Aspect religieux -- Islam.; Moyen-Orient -- Politique et gouvernement -- 21e siècle.; POLITICAL SCIENCE / World / Middle Eastern; Islamic fundamentalism; Jihad; Politics and government; Terrorism -- Religious aspects -- Islam; Middle East; 2000-2099; 2003 invasion of Iraq.; Abu Anas al-Shami.; Abu Ayyub al-Masri.; Abu Bakr al-Baghdadi.; Abu Fatima al-Jaheishi.; Abu Ghraib prison.; Abu Musab al-Zarqawi.; Abu Muslim al-Turkmani.; Abu Omar al-Baghdadi.; Abu Qatada.; Abu Yahya al-Libi.; Activism.; Adnan al-Aroor.; Ahrar al-Sham.; Al-Nusra Front.; Al-Qaeda in the Islamic Maghreb.; Al-Qaeda.; Al-Tawhid Brigade.; American-led intervention in Syria.; Ansar al-Islam.; Anti-Americanism.; Anti-Shi'ism.; Anwar al-Awlaki.; Apostasy.; Arab Spring.; Armed Islamic Group of Algeria.; Association of Muslim Scholars.; Ba'ath Party.; Ba'athism.; Blitzkrieg.; Caliphate.; Cataclysm (Dragonlance).; Combatant.; Counter-insurgency.; De-Ba'athification.; English Defence League.; Faith campaign.; Fall of Mosul.; Free Syrian Army.; General Military Council for Iraqi Revolutionaries.; God.; Gulf War.; Haji Bakr.; Haytham Manna.; Ideology.; Insurgency.; Iranian Revolution.; Iraq War.; Iraqis.; Islam.; Islamic Front for the Iraqi Resistance.; Islamic State of Iraq and the Levant.; Islamic State of Iraq.; Islamic extremism.; Islamism.; Izzat Ibrahim al-Douri.; Jama'at al-Tawhid wal-Jihad.; Jihadism.; Khawarij.; Khums.; Management of Savagery.; Mujahideen Shura Council (Iraq).; Mujahideen.; Muntada al-Ansar.; Muqtada al-Sadr.; Muslim Brotherhood in Egypt.; Muslims (nationality).; Nationalist faction (Spanish Civil War).; Oppression.; Osama bin Laden.; Peace Companies.; Peter Bergen.; Political Council for the Iraqi Resistance.; Popular Mobilization Forces.; Saddam Hussein.; Salafi jihadism.; Security dilemma.; Self-immolation.; Sharia.; Shia Islam.; Shock and awe.; Sons of Iraq.; Suicide attack.; Sunni Islam.